Breast milk – a living superfood. Review of current knowledge - Figurowska, Patrycja; Małek, Natalia; Emerla, Sara; Brożyna, Aleksandra; Kwiatkowska, Anita; Bydliński, Arkadiusz; Karłowicz, Konrad; Hermanowska, Maria; Lubomirska, Julia; Ciulkiewicz, Łukasz; et al. (Journal of Education, Health and Sport, 2024)
Introduction: Breastfeeding is considered the best nutrition for infants, including born preterm due to containing optimal ingredients for development and growth. Breast milk is a rich source of nutrients, it also contains diverse types of bacteria, which play a role in infant’s gastrointestinal tract colonization and preserving mammary health. Composition of human milk varies depending on numerous maternal and infant factors. Aim of the study: The aim of the study was to summarize the current knowledge about the content of nutrients, bioactive factors and microbiota diversity in human milk depending on various factors. Materials and methods: The work is a review of 26 mainly English-language scientific publications from 1989-2024 posted on the PubMed platform. Results: Milk composition changes in addition to several factors. Depending on postnatal age: preterm milk has higher content of protein, fat and immunological factors and lower concentration of lactose than term milk. Depending on milk maturity: Colostrum is higher in protein but lower in lactose, fat and energy than mature milk. Human milk is also a source of viable bacteria important for developing infant’s gut microbiota, but the diversity of bacterial strains in milk may vary. Depending on mode of delivery: milk of mothers after spontaneous labour contents more probiotic vaginal- and enteric-associated bacteria, while milk of mothers after C-section has more skin-associated microbiota. Depending on mother’s weight: milk of overweight mothers is lower in probiotic- and higher in pathogenic bacteria. Alcohol, nicotine, and some medications also have negative impact on produced milk. Conclusions: Human milk varies from woman to woman and its composition depends on several factors. Postnatal and gestational stage, delivery mode, mother’s weight and certain substances have been found to be important factors influencing the constitution of breast milk, including nutrients, microbiota and volume of milk.